Positive effects of Cordyceps cateniannulata colonization in tobacco: Growth promotion and resistance to abiotic stress - Qiao, Lu; Liu, Jing; Zhou, Zhengxiong; Li, Zhimo; Zhou, Yeming; Xu, Shaohuan; Yang, Zhengkai; Qu, Jiaojiao; Zou, Xiao (Frontiers in Microbiology, 2023)
Background: Entomopathogenic fungi can live in insects to cause disease and death and are the largest group of entomopathogenic microorganisms. Therefore, these fungi are best known for their microbial control potential. Importantly, they also have other beneficial effects, including promoting plant growth and development by colonizing plant. Here, the study sought to identify specific strains of the entomopathogenic fungus, Cordyceps cateniannulata that would form endophytic associations with tobacco, thus benefiting plant growth and resistance to abiotic stresses, thereby highlighting the application of entomopathogenic fungi in tobacco. Methods: The C. cateniannulata-tobacco symbiont was constructed by root irrigation. The effects of C. cateniannulata on tobacco growth were evaluated by measuring the maximum leaf length, maximum leaf width, number of leaves, plant height, stem thickness, stem circumference, dry and fresh shoot weight 7, 14, 21, and 28 d after colonization. The peroxidase, catalase, superoxide dismutase, and malondialdehyde were measured to observe the impact of C. cateniannulata on tobacco defense enzyme activity. Finally, high-throughput sequencing was used to access microbial communities in the rhizosphere, with data subsequently linked to growth indicators. Results: After tobacco was inoculated with C. cateniannulata X8, which significantly promoted growth and related enzyme activity, malondialdehyde was decreased. The most significant impact was on peroxidase, with its activity being upregulated by 98.20%, 154.42%, 180.65%, and 170.38% in the four time periods, respectively. The high throughput sequencing results indicated that C. cateniannulata had changed the rhizosphere microbial relative abundances, such as increasing Acidobacteria and Ascomycetes, and decreasing Actinomycetes and Basidiomycetes. The redundancy analysis showed that C. cateniannulata significantly boosted tobacco growth by reducing the abundance of specific dominant genera such as Stachybotrys, Cephalotrichum, Streptomyces, Isoptericola， and Microbacterium. Conclusions: Specific strains of C. cateniannulata can be introduced into host plants as endophytes, resulting in promotion of host plant growth and increased resistance to abiotic stress and microbial pathogens. The study provides a foundation for future studies of C. cateniannulata as an ecological agent.